Bone formation in mono cortical mandibular critical size defects after augmentation with two synthetic nanostructured and one xenogenous hydroxyapatite bone substitute – in vivo animal study. Issue 5 (3rd June 2015) - Dau, Michael; Kämmerer, Peer W.; Henkel, Kai‐Olaf; Gerber, Thomas; Frerich, Bernhard; Gundlach, Karsten K. H.
Abstract: Objectives: Healing characteristics as well as level of tissue integration and degradation of two different nanostructured hydroxyapatite bone substitute materials (BSM) in comparison with a deproteinized hydroxyapatite bovine BSM were evaluated in an in vivo animal experiment. Material and methods: In the posterior mandible of 18 minipigs, bilateral mono cortical critical size bone defects were created. Randomized augmentation procedures with NanoBone ® (NHA1), Ostim ® (NHA2) or Bio‐Oss ® (DBBM) were conducted (each material n  = 12). Samples were analyzed after five (each material n  = 6) and 8 months (each material n  = 6). Defect healing, formation of soft tissue and bone as well as the amount of remaining respective BSM were quantified both macro‐ and microscopically. Results: For NHA2, the residual bone defect after 5 weeks was significantly less compared to NHA1 or DBBM. There was no difference in residual BSM between NHA1 and DBBM, but the amount in NHA2 was significantly lower. NHA2 also showed the least amount of soft tissue and the highest amount of new bone after 5 weeks. Eight months after implantation, no significant differences in the amount of residual bone defects, in soft tissue or in bone formation were detected between the groups. Again, NHA2 showed significant less residual material than NHA1 and DBBM. Discussion: We observed non‐significant differences in the biological hard tissue response of NHA1 and DBBM. The water‐soluble NHA2 initially induced an increased amount of new bone but was highly compressed which may have a negative effect in less stable augmentations of the jaw.